The Mediating Effect of Work Engagement on the Influence of Career Development on Organizational Citizenship Behavior at the Personnel and Human Resource Development Agency of Western Seram Regency - Fellin A. Luhukay; Tehubijuluw Zacharias; Elake Nataniel (MAN 4 Kota Pekanbaru, 2025)
This study examines the mediating role of work engagement in the relationship between career development and Organizational Citizenship Behavior (OCB) at the Personnel and Human Resource Development Agency of West Seram Regency. Using a quantitative, explanatory research design, data were collected through a structured questionnaire and analyzed using multiple regression and Sobel mediation tests. The results show that career development significantly improves OCB, and this effect becomes stronger when work engagement acts as a mediator. Employees who experience clear career pathways, competency-based development, and fair promotion systems tend to exhibit higher levels of vigor, dedication, and absorption, which in turn encourage voluntary behaviors beyond formal job roles. The findings also indicate that work engagement plays a substantial role in shaping positive employee behavior, serving as a psychological link between career development policies and OCB. The study highlights the importance of aligning career development initiatives with engagement strategies to enhance organizational performance in the public sector.